PROGRAM GURU MENULIS: UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU SEJARAH DALAM PENULISAN KARYA ILMIAH DI KABUPATEN SEMARANG - Sodiq, Ibnu; Suryadi, Andy; Ahmad, Tsabit Azinar (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2014)
The purpose of this activity is (1) Adding insight and understanding of the history teacher to many types of scientific kara; (2) Stimulate the spirit of the teacher to develop competence particularly in the field of scientific writing; (3) Stimulating new ideas and teachers in scientific writing for the purposes of education and professional development; (4) Introduce and help teachers publish scientific papers in journals ilmiah.Kegiatan training was conducted by the method of seminars and workshops. Implementation of detailed training is divided into several activities, namely: (1) Presentation on the various themes that can be developed in the writing of scientific papers; (2) Presentation of the systematic writing scientific papers and procedures writing in scientific journals; (3) A discussion of various issues related to the material presented; (4) Assignment yan manufacture of scientific work was accompanied by a team of devotion; (5) Assistance and evaluation by both parties or by the PPM Team History MGMPs Semarang.Setelah District conducted a series of training, participants know the significance kmpetensi professional development through the development of a scientific article.